CONVENTIONAL VS DIGITAL IMPRESSION TECHNIQUE FOR MANUFACTURING OF THREE-UNIT ZIRCONIA BRIDGES: CLINICAL TIME EFFICIENCY - Kiril Gogushev; Metodi Abadjiev (Peytchinski Publishing, 2021)
Introduction: Taking an impression of the oral cavity, which accurately recreates the prosthetic field, the surrounding hard dental and soft tissues, is one of the main and most important stages in the process of making any fixed prosthetic restoration. In modern prosthetic dentistry, impressions taken with the help of polyether and vinyl polysiloxane impression materials are common. Digital impressions eliminate some of the steps of conventional impression techniques and save clinical time. Aim: The aim of this article is to compare the clinical time in digital and conventional impression techniques from a whole dental arch using a controlled clinical trial. Material and methods: The present study includes 36 patients from Varna who need prosthetic treatment with fixed 3-unit bridge construction. For all participants, the conventional impression technique was performed first and one week later - the digital one. All clinical manipulations related to the implementation of the two impression techniques were performed according to the instructions of the manufacturing companies by the same specialist dentist. Results: In all participants, the time required to perform the digital impression technique is significantly less than that of the conventional impression technique. Conclusion: The digital impression technique has proven to be more efficient in terms of clinical time required for its implementation than the conventional impression technique.